Block poly(arylene ether sulfone) copolymers bearing quaterinized aromatic pendants: Synthesis, property and stability. (19th October 2017) - Zhang, Xueliang; Chen, Pei; Shi, Qian; Li, Songsong; Gong, Feixiang; Chen, Xinbing; An, Zhongwei
Abstract: Block poly(arylene ether sulfone) copolymers caring pendent benzyl-quaternary ammonium groups were prepared through multiple-step reaction pathways that involve pre-polycondensation, block copolycondensation, bromomethylation and Menshutkin reactions. The copolymer ionomer based anion exchange membranes (AEMs) with ion exchange capacity (IEC) from 0.75 to 1.10 mequiv g −1 display relatively large hydroxide conductivities of 45.9–66.1 mS cm −1 at 80 °C, which are ascribed to the distinct hydrophobic/hydrophilic microphase separation resulted from the block copolymer structures and side-chain type hydrophilic segments. Compared to the corresponding random copolymer based AEM, the block ones have obviously higher stability and larger hydroxide conductivity due to the well-connected ionic nanochannels. Among the AEMs, bQPAE-x7y32 with IEC of 1.10 mequiv g −1 gives the best performance with high hydroxide conductivity of 66.1 mS cm −1, low methanol permeability of 4.9 × 10 −7  cm 2  s −1, large φ of 4.6 × 10 4  Scm −3  s, as well as good alkaline stability, respectively. Highlights: Block PAE copolymers with quaterinized aromatic pendants are developed. Good hydroxide conductivity is ascribed to the distinct microphase separation. High alkaline stability is attributed to block copolymer and side-chain structures. Decomposition of ionic groups is mainly caused by nucleophilic substitution.